“Eficacia de las técnicas de cepillado dental fones y stillman para disminuir la placa bacteriana en adolescentes”. - Toapanta Quinatoa, Miriam Margoth (2017)
The present research project focuses on compaing dental brushing techniques Fones and Stillman to decrease bacterial plaque in adolescents. The study was carried out in the Educational Unit "San José de Guaytacama" in Latacunga with a group of 50 students between 15 and 17 years of age. The type and design of the study was comparative, longitudinal, because several comparison scenes were made and the changes produced in the same sample at a time were studied. They were divided into two groups of 25 students for each one, the first group used the technique of Fones and the second one of Stillman, and the data obtained were recorded in the O’Leary index. All participants in the study at the end of the investigation had an acceptable level of bacterial plaque. Because in the case of the brushing technique of Fones 19 cases of acceptable oral hygiene (76%) were obtained, while the remaining 6 cases (24%) were deficient. On the other hand, in the Stillman technique, 22 individuals achieved an acceptable level of oral hygiene (88%) and 3 deficient (12%). It was also observed that the evolution of the treatment is favorable, because from the third week 38% of the cases presented a removal of plaque and the fourth week in 82% in adolescents. On the other hand, it is possible to mention that the technique of Stillman allows to remove the plaque bacteriana in less time.